2016
DOI: 10.1002/anie.201511351
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into the Allosteric Inhibition of the SUMO E2 Enzyme Ubc9

Abstract: Conjugation of the small ubiquitin-like modifier (SUMO) to protein substrates is an important disease-associated posttranslational modification, though few inhibitors of this process are known. Here, we report the discovery of an allosteric small molecule binding site on Ubc9, the sole SUMO E2 enzyme. An X-ray crystallographic screen was used to identify two distinct small molecule fragments that bind to Ubc9 at a site distal from its catalytic cysteine. These fragments and related compounds inhibit SUMO conju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…In addition to wildtype enzyme, two Ubc9 mutants (K59A and E42A) that disrupt a recently identified allosteric site were evaluated. 6 Compound 2 was able to inhibit SUMO conjugation to the fluorescent peptide substrate for all three enzymes without any apparent change in potency (Suppl. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to wildtype enzyme, two Ubc9 mutants (K59A and E42A) that disrupt a recently identified allosteric site were evaluated. 6 Compound 2 was able to inhibit SUMO conjugation to the fluorescent peptide substrate for all three enzymes without any apparent change in potency (Suppl. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The in vitro sumoylation assay was performed in 20 μL reaction buffer (50 mM Tris [pH 9], 5 mM MgCl 2 , 1 mM DTT) containing SUMO E1 (0.1 μM), Ubc9 (0.15 μM), SUMO-1 (His-tag, 1.4 μM), and a fluorescent peptide (FL-AR) substrate 5 (1 μM) incubated with various concentrations of small molecule in DMSO or DMSO alone (4% final concentration). Experiments with mutant Ubc9, obtained as previously described, 6 were conducted according to the same procedure using K59A or E42A Ubc9 in place of the wild-type E2. The reaction was then initiated by the addition of ATP (2 mM final concentration) and incubated at room temperature for 90 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Biochemical, structural and computational studies have revealed how RING/U-box E3s stimulate internal dynamics in different E2s that are linked to their ubiquitination activity (Benirschke et al, 2010; Chakrabarti et al, 2017; Das et al, 2013; Ozkan et al, 2005). Furthermore, recent efforts in fragment-based inhibitor discovery have revealed promising lead compounds that bind Ube2T (Morreale et al, 2017) as well as the unrelated Ube2I (Hewitt et al, 2016) at regions distal from their active/E3 binding sites, nevertheless can allosterically regulate the respective E2 activities. These observations collectively suggest that allosteric networks could operate across the E2 family and that future investigations into such networks could prove instrumental for basic and translational research in ubiquitin biology.…”
Section: Discussionmentioning
confidence: 99%